2016
DOI: 10.1021/acsami.5b11349
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Substrate Temperature-Induced Growth Modes of Organic Semiconductors at Dielectric/semiconductor Interface and Their Correlation with Threshold Voltage Stability in Organic Field-Effect Transistors

Abstract: Influence of substrate temperature on growth modes of copper phthalocyanine (CuPc) thin films at the dielectric/semiconductor interface in organic field effect transistors (OFETs) is investigated. Atomic force microscopy (AFM) imaging at the interface reveals a change from 'layer+island' to "island" growth mode with increasing substrate temperatures, further confirmed by probing the buried interfaces using X-ray reflectivity (XRR) and positron annihilation spectroscopic (PAS) techniques. PAS depth profiling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Thermal annealing experiments addressed the molecular reorganization after growth (Hinderhofer et al, 2012;Duva et al, 2019;Chiodini, D'Avino et al, 2020), which influences the roughness as well. The increasing island sizes at decreasing island densities as a result of heated substrates during growth are confirmed by a previous study on CuPc (Jungyoon et al, 2003;Padma et al, 2016) and were also found for another molecule named parahexaphenyl (6P) (Frank & Winkler, 2008). Finally, the assumption that different polymorphs and molecular orientations coexist in CuPc thin films is justified and corroborated by the reported continuous transitions between different CuPc polymorphs (Heutz et al, 2000;Berger et al, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Thermal annealing experiments addressed the molecular reorganization after growth (Hinderhofer et al, 2012;Duva et al, 2019;Chiodini, D'Avino et al, 2020), which influences the roughness as well. The increasing island sizes at decreasing island densities as a result of heated substrates during growth are confirmed by a previous study on CuPc (Jungyoon et al, 2003;Padma et al, 2016) and were also found for another molecule named parahexaphenyl (6P) (Frank & Winkler, 2008). Finally, the assumption that different polymorphs and molecular orientations coexist in CuPc thin films is justified and corroborated by the reported continuous transitions between different CuPc polymorphs (Heutz et al, 2000;Berger et al, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…16,17,20,24 At high substrate temperatures, molecules have increased kinetic energy and are able to easily migrate to lower energy sites creating nucleation points, resulting in polycrystalline structures with large crystallites and fewer grain boundaries. 24,28,29 This phenomenon has been well documented in MPcs [28][29][30][31][32][33][34][35][36] which at room temperature exhibit ne grained morphologies, whereas large rod-like bers occur at increasing substrate temperatures, as exhibited by scanning electron microscopy (SEM) and atomic force microscopy (AFM) images of copper phthalocyanine (CuPc) in Fig. 4.…”
Section: Nucleation Densitymentioning
confidence: 80%
“…4i). 30,31,[34][35][36] At very low temperatures (<0 C) the surface mobility and diffusion are decreased such that molecules lack the energy required to nd favourable nucleation cites, and amorphous lms are formed, as illustrated by low temperature depositions of pentacene. 23,37,38 Fig.…”
Section: Nucleation Densitymentioning
confidence: 99%
“…26,27 However, increasing the substrate temperature beyond the optimum may result in island-mode growth or desorption of semiconductor molecules from the surface. 28 In Section 3.1, we investigate how the substrate temperature during the DPh-BTBT deposition affects the DPh-BTBT film growth and the characteristics of TFTs fabricated on silicon and on flexible PEN substrates, and based on this information, DPh-BTBT TFTs were fabricated on the respective substrates with different fluoroalkylphosphonic acids forming the gate dielectric SAM. Section 3.2 examines the influence of the chain length of the fluoroalkylphosphonic acid on the semiconductor morphology and the TFT performance.…”
Section: Resultsmentioning
confidence: 99%